1996
DOI: 10.1063/1.470965
|View full text |Cite
|
Sign up to set email alerts
|

Order–disorder transition and ordering kinetics in binary diblock copolymer mixtures of styrene and isoprene

Abstract: Monte Carlo simulation of the order-disorder transition of a symmetric cyclic diblock copolymer systemThe order-disorder transition ͑ODT͒ and the ordering kinetics have been studied in two symmetric diblock copolymers of styrene and isoprene and their binary mixtures with rheology. The binary mixtures formed a single microdomain ͑with lamellar morphology͒ composed of short and long chains as confirmed by small angle x-ray scattering ͑SAXS͒. The order-disorder transition temperature ͑T ODT ͒, obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 18 publications
8
70
1
Order By: Relevance
“…Rosedale and Bates 9 followed the kinetics of the disorder-to-order transition in a poly(methylbutylene)-block-poly(ethylethylene) copolymer melt with time-resolved rheology and found that the kinetics slowed down monotonically with increasing temperature. Floudas et al 10 estimated the time required to complete the disorderto-order transition in a polystyrene-block-polyisoprene copolymer melt by the same method and found the same result: slower kinetics at higher temperatures. This suggests that in both cases, 9,10 the experiments were conducted at T Ͼ T max ; that is, order formation was controlled by thermodynamic factors.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Rosedale and Bates 9 followed the kinetics of the disorder-to-order transition in a poly(methylbutylene)-block-poly(ethylethylene) copolymer melt with time-resolved rheology and found that the kinetics slowed down monotonically with increasing temperature. Floudas et al 10 estimated the time required to complete the disorderto-order transition in a polystyrene-block-polyisoprene copolymer melt by the same method and found the same result: slower kinetics at higher temperatures. This suggests that in both cases, 9,10 the experiments were conducted at T Ͼ T max ; that is, order formation was controlled by thermodynamic factors.…”
Section: Introductionmentioning
confidence: 84%
“…Floudas et al 10 estimated the time required to complete the disorderto-order transition in a polystyrene-block-polyisoprene copolymer melt by the same method and found the same result: slower kinetics at higher temperatures. This suggests that in both cases, 9,10 the experiments were conducted at T Ͼ T max ; that is, order formation was controlled by thermodynamic factors. This is surprising when one considers the fact that the experiments on the polystyrene-block-polyisoprene copolymer 10 were conducted at temperatures between 74 and 86°C.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this respect, the true ODT is the so-called equilibrium ODT [67]. The kinetics of ordering of block copolymers has been studied in great detail using combination of shear rheology and time-resolved small-angle X-ray scattering (SAXS) experiments [66,[68][69][70][71]. In general, the results are well described by the Avrami equation that also applies to the kinetics of crystallization.…”
Section: Disorder-to-order Transitionsmentioning
confidence: 99%